(untitled) (World Bulletin of Public Health, 2024)
This article describes in detail the effects of energy drinks, one of the most popular soft drinks, on the mechanism of heart function, muscle contraction, pulse and blood composition. With the increase in energy drink consumption over the past decade, the number of energy drink users among emergency department employees has also increased significantly. That is, there is alcohol poisoning, arrhythmia, increased blood pressure and heart rate. To observe these effects, we conducted a study among our peers